Spatio-temporal dynamics of genetic diversity in Sorghum bicolor in Niger - Deu, M.; Sagnard, F.; Chantereau, J.; Calatayud, C.; Vigouroux, Yves; Pham, J.L.; Mariac, C.; Kapran, I.; Mamadou, A.; Gerard, Bruno G.; Ndjeunga, J.; Bezançon, G. (Springer, 2010)
The dynamics of crop genetic diversity need to be assessed to draw up monitoring and conservation priorities. However, few surveys have been conducted in centres of diversity. Sub-Saharan Africa is the centre of origin of sorghum. Most Sahel countries have been faced with major human, environmental and social changes in recent decades, which are suspected to cause genetic erosion. Sorghum is the second staple cereal in Niger, a centre of diversity for this crop. Niger was submitted to recurrent drought period and to major social changes during these last decades. We report here on a spatio-temporal analysis of sorghum genetic diversity, conducted in 71 villages covering the rainfall gradient and range of agro-ecological conditions in Niger’s agricultural areas. We used 28 microsatellite markers and applied spatial and genetic clustering methods to investigate change in genetic diversity over a 26-year period (1976–2003). Global genetic differentiation between the two collections was very low (F st = 0.0025). Most of the spatial clusters presented no major differentiation, as measured by F st, and showed stability or an increase in allelic richness, except for two of them located in eastern Niger. The genetic clusters identified by Bayesian analysis did not show a major change between the two collections in the distribution of accessions between them or in their spatial location. These results suggest that farmers’ management has globally preserved sorghum genetic diversity in Niger.